If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + x = -8x + -18 Reorder the terms: 9 + x = -18 + -8x Solving 9 + x = -18 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 9 + x + 8x = -18 + -8x + 8x Combine like terms: x + 8x = 9x 9 + 9x = -18 + -8x + 8x Combine like terms: -8x + 8x = 0 9 + 9x = -18 + 0 9 + 9x = -18 Add '-9' to each side of the equation. 9 + -9 + 9x = -18 + -9 Combine like terms: 9 + -9 = 0 0 + 9x = -18 + -9 9x = -18 + -9 Combine like terms: -18 + -9 = -27 9x = -27 Divide each side by '9'. x = -3 Simplifying x = -3
| X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 |